Carbon-coated current collector, preparation method and application thereof
Patent Information
- Application Number
- CN202511648418.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-11
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2045-11-11
AI Technical Summary
[0005]然而,涂炭集流体中,基材边缘涂覆的边涂浆料与基材中间涂覆的涂炭浆料通常会存在一定程度的互溶现象,这样既会使涂炭浆料形成的涂炭区导电性下降,又会使边涂浆料所形成的绝缘区绝缘性能下降,从而影响锂电池的电化学性能以及安全性能
本发明通过在涂炭集流体基材两侧的绝缘区所采用的水性浆料中引入有机物,该有机物可以在绝缘区的水性浆料表面形成一层稳定、连续的油性膜,因此可以有效阻隔涂炭区的水性浆料以及绝缘区的水性浆料这两种水性浆料,即有效避免这两种水性浆料的互溶现象,进而有效保证了所形成的涂炭区的导电性能以及绝缘区(第一绝缘区、第二绝缘区)的绝缘性能,使由该涂炭集流体所制备的电池具有更好的电化学性能以及绝缘性能。
Smart Images

Figure CN121617973B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium battery current collector technology, specifically relating to a carbon-coated current collector, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries (LIBs) have been widely adopted in various fields such as consumer electronics, transportation, power tools, and energy storage. Aluminum or copper foil current collectors refer to the process of combining aluminum or copper foil with other materials (such as paper, plastic film, coatings, etc.) to form a composite material. This technology can endow aluminum or copper foil with new properties and functions to meet the needs of different industries.
[0003] Furthermore, to improve the performance of lithium batteries, the lithium battery industry employs a strategy of using carbon-coated current collectors to increase the rate of operation and overall performance. However, if the edges of the carbon-coated current collector are not insulated, poor electrode alignment or incomplete separator coverage during battery assembly may lead to a short circuit between the positive and negative electrodes.
[0004] Therefore, to improve the safety of lithium-ion battery current collectors, the current main approach is to apply a ceramic edge coating to the edges of the carbon-coated current collector. This edge coating involves applying ceramic slurry to the edges of the carbon-coated current collector, a measure of significant importance in lithium-ion battery manufacturing: 1. Safety: Directly reduces the risk of short circuits and thermal runaway, meeting the high safety standards of power batteries (such as electric vehicles). 2. Lifespan Improvement: Reduces edge side reactions (such as lithium plating and corrosion), extending cycle life. 3. High Energy Density Design: Edge protection allows for more aggressive optimization of electrode thickness or material systems. Therefore, the core purpose of edge coating on carbon-coated current collectors is to "eliminate edge risks and improve battery reliability and performance," a key step in detail optimization during battery manufacturing, especially important in high-end applications (such as power batteries and high-nickel systems).
[0005] However, in carbon-coated current collectors, there is usually a certain degree of mutual solubility between the edge coating slurry applied to the edge of the substrate and the carbon coating slurry applied in the middle of the substrate. This will reduce the conductivity of the carbon coating area formed by the carbon coating slurry and reduce the insulation performance of the insulating area formed by the edge coating slurry, thereby affecting the electrochemical performance and safety performance of the lithium battery. Summary of the Invention
[0006] To address the problems and shortcomings of existing technologies, this invention provides a carbon-coated current collector, its preparation method, and its application. The carbon-coated current collector has insulating regions on both sides of its substrate edge, and no significant mutual dissolution occurs at the junction of the insulating regions on both sides and the carbon-coated region in the middle. Therefore, it can effectively ensure the conductivity of the carbon-coated region edge and the insulation performance of the insulating region edge, which is beneficial to ensuring the electrochemical performance and safety performance of the battery using the carbon-coated current collector.
[0007] According to a first aspect of the present invention, a carbon-coated current collector is provided, comprising a substrate and a functional layer disposed on at least one side surface of the substrate; the functional layer includes a first insulating region, a carbon-coated region, and a second insulating region; the first insulating region, the carbon-coated region, and the second insulating region are arranged sequentially in the width direction of the substrate, and the first insulating region and the second insulating region are respectively located at the two side edges in the width direction of the substrate; the first insulating region and the second insulating region have a surface tension of 10~32 mN / m at room temperature and a density of less than 1.0 g / cm³ at room temperature. 3 Organic matter.
[0008] Currently, the main improvement strategies for edge coating (side coating) of carbon-coated current collectors include two approaches: using oil-based slurries and water-based slurries to form an edge insulation zone. Oil-based slurries mostly use organic solvents such as NMP, but organic solvents typically have poor environmental performance. For environmental reasons, many manufacturers are considering developing and focusing on water-based edge coating slurries using pure water as a solvent. However, most carbon coating slurries also use water as a solvent, leading to varying degrees of miscibility between the two slurries during coating. Miscibility between the two water-based slurries can have serious consequences. For example, if carbon coating slurry dissolves into the edge coating slurry, it will reduce the insulation of the edge coating slurry, affecting safety; conversely, if edge coating slurry mixes into the carbon coating slurry, it will reduce the conductivity of the sample, affecting the lithium battery's electrical performance. Therefore, solving the miscibility problem between water-based edge coating slurries and water-based carbon coating slurries is extremely important.
[0009] Therefore, in the carbon-coated current collector provided by the present invention, an organic material with low surface tension and a density lower than water at room temperature is introduced into the slurry material required to form the first insulation zone and the second insulation zone. This organic material is immiscible with the solvent water in the aqueous slurry and can float on water. Therefore, during the process of simultaneously coating or applying the aqueous slurry of the carbon coating area and the aqueous slurry of the insulating area to the middle and the edge of the substrate, since the density of organic matter is less than that of water, the organic matter in the aqueous slurry of the insulating area will float on the surface of the aqueous slurry of the insulating area. Moreover, the organic matter does not dissolve in water. Therefore, at the junction of the aqueous slurry of the carbon coating area and the aqueous slurry of the insulating area, that is, on the surface of the aqueous slurry of the insulating area, the organic matter will form an oil film. This oil film can effectively block the two types of aqueous slurry, thus effectively avoiding the phenomenon of mutual dissolution between the two types of aqueous slurry. This effectively ensures the conductivity of the carbon coating area and the insulation performance of the insulating areas (first insulating area and second insulating area), so that the battery prepared by the carbon coating current collector has better electrochemical performance and insulation performance.
[0010] It should be noted that, taking a wound cell as an example, the width direction of the carbon-coated current collector is consistent with the width direction of the positive and negative electrode plates, and the edge of the carbon-coated current collector in the width direction is connected to the tab.
[0011] Preferably, the surface tension of the organic material at room temperature is 15~25 mN / m. Further limiting the surface tension of the organic material to this range is more conducive to forming a stable barrier layer on the surface of the insulating area, while ensuring the uniformity of the dispersion of the second slurry (side coating slurry), and further improving the conductivity of the carbonized area of the carbonized current collector and the insulation of the insulating areas on both sides. If the surface tension is too low, firstly, the organic material will be difficult to disperse uniformly in the aqueous slurry, easily agglomerating into large particles or clusters, reducing the uniformity of the slurry and affecting its overall stability. This is also detrimental to the uniformity of the formed insulating area, reducing its insulation performance. Secondly, it will result in a larger interfacial tension between the organic material and the aqueous slurry. This larger interfacial tension will make the oil film unstable at the interface, easily breaking or forming a discontinuous film, thus failing to effectively prevent the mutual solubility of the two aqueous slurries, and therefore deteriorating the conductivity of the carbonized area and the insulation of the insulating area.
[0012] Preferably, the dielectric constant of the organic material is 1 to 5. Within this range, the organic material exhibits high electrical insulation properties, effectively preventing charge leakage and discharge, thus further enhancing the insulation performance of the insulating region. Preferably, the dielectric constant of the organic material is 2 to 3. The dielectric constant is obtained under normal temperature (25°C) and frequency (1 kHz) conditions.
[0013] Preferably, the volume resistivity of the organic material is 10. 14 ~10 16 Ω·cm. The test conditions for volume resistivity are: test voltage: 100V, electrochemical time: 60s, test temperature: 23℃, humidity: ≤50%RH.
[0014] Preferably, the breakdown voltage of the organic material is 15–30 kV / mm. The test conditions for the breakdown voltage are: refer to IEC 60156, voltage: 50Hz AC, temperature: 26℃.
[0015] Preferably, the organic material includes at least one of dimethyl silicone oil, perfluoropolyether oil, perfluorohexane, fluorinated silicone oil, and long-chain alkanes. These substances can form a relatively stable, continuous, and uniform oil film at the interface of the two aqueous slurries, thus effectively preventing the miscibility of the two aqueous slurries and ensuring good conductivity in the carbon-coated area and good insulation in the insulating area. Preferably, the long-chain alkanes include polyα-olefins.
[0016] Preferably, the first and second insulating zones further contain insulating material, with a mass ratio of insulating material to organic matter of 5-15:0.5-3. Maintaining this mass ratio within the above range ensures an appropriate amount of organic matter in the aqueous slurry forming the insulating zones. This avoids situations where insufficient organic matter leads to discontinuous or insufficiently thick oil film, poor stability, and susceptibility to external damage, failing to effectively prevent the miscibility of the two aqueous slurries. Conversely, excessive organic matter results in poor slurry dispersibility, affecting the slurry's functionality, such as its insulating properties. Furthermore, a mass ratio of insulating material to organic matter within the above range is more conducive to the overall dispersibility and long-term stability of the slurry. Preferably, the organic compound includes dimethyl silicone oil. More preferably, the organic compound is dimethyl silicone oil.
[0017] Preferably, the width of the first insulating region and the second insulating region is 1~5cm; the width of the carbon coating region is greater than or equal to 20cm. Controlling the coating width of the insulating regions on both sides is beneficial to balance the conductivity and insulation properties of the carbon coating current collector.
[0018] Preferably, in the functional layer, the thickness of the first insulating region and the second insulating region is 1~3μm, and the thickness of the carbon-coated region is 1~3μm. Preferably, in the functional layer, the thickness of the first insulating region, the second insulating region, and the carbon-coated region is the same.
[0019] Preferably, the functional layers are disposed on both sides of the substrate.
[0020] Preferably, the insulating material includes at least one selected from boehmite, barium sulfate, alumina, silicon carbide, silicon nitride, zirconium oxide, and boron oxide. Preferably, the insulating material includes boehmite and barium sulfate; and the mass ratio of boehmite to barium sulfate is 6-9:1-4. The combination of boehmite and barium sulfate in the insulating material provides better insulation performance, while barium sulfate has higher hardness (Mohs hardness 3-3.5) and chemical stability, which can improve the mechanical strength of the edge coating and reduce edge wear of the electrode during slitting, winding, or charging and discharging. Therefore, the combination of the two is more conducive to balancing the insulation performance and mechanical stability of the coating. At the same time, ensuring that the amount of boehmite is slightly larger than the amount of barium sulfate not only improves the insulation performance of the insulating area but also benefits the dispersion stability of the slurry, thus further improving the uniformity of the insulating area formed by the second slurry and enhancing the edge insulation performance of the carbon-coated current collector.
[0021] Preferably, the mass ratio of boehmite to barium sulfate is 9:1.
[0022] Preferably, the substrate includes at least one of aluminum foil and copper foil. Preferably, the substrate includes aluminum foil.
[0023] Preferably, the carbon coating zone includes a first binder and a conductive agent; the mass ratio of the first binder, the conductive agent, and the first wetting agent is 1~2:1~3:1~2.
[0024] Preferably, the first binder comprises at least one selected from polyacrylic acid, ethyl polyacrylate, butyl polyacrylate, acrylate copolymers, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyvinyl acetate. Preferably, the first binder comprises polyacrylic acid, and the polyacrylic acid is added as a polyacrylic acid emulsion, the solid content of the polyacrylic acid emulsion being 15-30%, and the viscosity being 800-3500 mPa·s. The solid content of the polyacrylic acid emulsion is, for example, 15%, 16%, 17%, 18%, 20%, 22%, 25%, or 30%, but is not limited to the listed values; other unlisted values within the range also apply. The viscosity of the polyacrylic acid emulsion is, for example, 800 mPa·s, 850 mPa·s, 900 mPa·s, 950 mPa·s, 1000 mPa·s, 1050 mPa·s, 1100 mPa·s, 1200 mPa·s, 1300 mPa·s, 1400 mPa·s, 1500 mPa·s, 2000 mPa·s, 2500 mPa·s, 3000 mPa·s, or 3500 mPa·s, but is not limited to the listed values; other unlisted values within the range also apply.
[0025] Preferably, the conductive agent includes at least one selected from carbon powder, graphite, carbon black, carbon nanotubes, carbon nanofibers, and graphene. Preferably, the conductive agent includes carbon powder and graphite, with a mass ratio of carbon powder to graphite of 0.8~1.5:0.8~1.5.
[0026] Preferably, the first wetting agent and the second wetting agent independently comprise at least one of polyether siloxane, modified polyether siloxane, and alcohol reagent. Preferably, the first wetting agent and the second wetting agent independently comprise modified polyether siloxane. Modified polyether siloxane is available from Evonik under the model name TEGO® Glide 410.
[0027] Preferably, the first insulating region and the second insulating region further include a second adhesive, and the mass ratio of the second adhesive, insulating material and organic matter is 15~25:5~15:0.5~4.
[0028] Preferably, the second binder comprises at least one selected from polyacrylic acid, ethyl polyacrylate, butyl polyacrylate, acrylate copolymers, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyvinyl acetate. Preferably, the second binder comprises polyacrylic acid, and the polyacrylic acid exists as a polyacrylic acid emulsion with a solid content of 15-30% and a viscosity of 800-3500 mPa·s.
[0029] According to a second aspect of the present invention, a method for preparing the above-mentioned carbon-coated current collector is provided, characterized in that the specific operation is as follows: a first slurry and a second slurry are simultaneously coated on the surface of a substrate to form a functional layer containing a first insulating region, a carbon-coated region, and a second insulating region arranged sequentially in the width direction of the substrate; wherein the carbon-coated region is formed using the first slurry, and the first insulating region and the second insulating region are formed using the second slurry; the first slurry includes a first binder, a conductive agent, and a first wetting agent; the mass ratio of the first binder, the conductive agent, and the first wetting agent is 1~2:1~3:1~2; the second slurry includes a second binder, an insulating material, a second wetting agent, and an organic substance, the mass ratio of the second binder, the insulating material, the second wetting agent, and the organic substance is 15~25:5~15:0.2~0.8:0.5~3.
[0030] Simultaneous coating with the first and second slurries helps ensure that the formed carbonized and insulating areas have similar thicknesses, ensures that there are no obvious defects at the interface between the carbonized and insulating areas, improves the overall uniformity of the functional layer, and thus helps the carbonized and insulating areas in the functional layer to perform better, ensuring that the battery has better electrochemical and safety performance.
[0031] Preferably, the first slurry is prepared by the following steps: S11. Mixing water and a first binder until homogeneous to obtain mixture A1; S12. Adding a first portion of conductive agent to mixture A1 until homogeneous to obtain mixture A2; the first portion of conductive agent constitutes 40-60% of the total mass of the conductive agent; S13. Adding a second portion of conductive agent to mixture A2 until homogeneous to obtain mixture A3; the second portion of conductive agent constitutes 40-60% of the total mass of the conductive agent; the first portion of conductive agent and the second portion of conductive agent... The mass of each component is added together to obtain the total mass of the conductive agent; S14. Water is added to mixture A3 to reduce the slurry concentration, and after mixing evenly, mixture A4 is obtained; S15. The first pH adjuster is added to mixture A4, and after mixing evenly, the pH of the resulting mixture A5 is 5~7; S16. The first wetting agent is added to mixture A5, and after mixing evenly, mixture A6 is obtained; S17. Mixture A6 is homogenized, and the pressure of the homogenizing equipment during the homogenization process is 250~400 bar, to obtain the first slurry.
[0032] Preferably, in the preparation method of the carbon-coated current collector, any one of the following conditions is met: (1) The second slurry further includes a second solvent, with the surface tension difference between the second organic solvent and the organic material being k, k=30~60; preferably, k=50~60; (2) The first slurry further includes a first solvent, with the surface tension difference between the first solvent and the organic material being m, m=30~60; preferably, m=50~60; (3) The second slurry further includes a second solvent, and the first slurry further includes a first solvent, with the surface tension difference between the second solvent and the first solvent being n, n=0~20; preferably, n=0~5. In particular, when the difference between the surface tension of the organic material and the second organic solvent is within the above range, the organic material can better aggregate into a film on the surface of the second slurry, so that the dried insulating area and the carbon-coated area have strong barrier properties. Similarly, when the surface tension difference between the organic material and the first organic solvent is within the aforementioned range, the organic material will not be dissolved by the first slurry when it accumulates on the surface and comes into contact with it, thus better ensuring the barrier performance between the dried insulating area and the carbonized area. Furthermore, when the surface tension difference between the second solvent and the first solvent is within the aforementioned range, it is more conducive to forming a smooth surface in both the insulating and carbonized areas, preventing noticeable unevenness at the interface and thereby optimizing the overall performance of the current collector. Preferably, the first solvent includes water. Water has a surface tension of 72.0 mN / m at room temperature (25°C).
[0033] Preferably, the second solvent includes water.
[0034] Preferably, in S11, during the mixing process, the stirring rate is 500-600 rpm / min and the stirring time is 8-15 min.
[0035] Preferably, in S12, during the mixing process, the stirring rate is 2000-2600 rpm / min, and the stirring time is 20-50 min.
[0036] Preferably, in S13, during the mixing process, the stirring rate is 2000-2600 rpm / min, and the stirring time is 40-90 min.
[0037] Preferably, in S14, during the mixing process, the stirring rate is 2000-2600 rpm / min, and the stirring time is 20-50 min.
[0038] Preferably, in step S15, the amount of the first pH adjuster added is calculated to adjust the pH of the first slurry to 5-7. Preferably, the first pH adjuster includes at least one of sulfuric acid and hydrochloric acid.
[0039] Preferably, in S16, during the mixing process, the stirring rate is 10-15 rpm / min and the stirring time is 30-45 min.
[0040] Preferably, in step S17, the homogenization is performed at least twice. Preferably, in the first slurry, the mass ratio of the first binder, conductive agent, first wetting agent, and water is 1~2:1~3:1~2:20~30.
[0041] Preferably, the second slurry is prepared by the following steps: S21. Mixing water and the second binder evenly to obtain mixture B1; S22. Adding the first part of the insulating material to mixture B1 and mixing evenly to obtain mixture B2; the first part of the insulating material accounts for 40-60% of the total mass of the insulating material; S23. Adding the second part of the insulating material to mixture B2 and mixing evenly to obtain mixture B3; the second part of the insulating material accounts for 40-60% of the total mass of the insulating material; the mass of the first part of the insulating material plus the mass of the second part of the insulating material... S24. Add water to mixture B3 to reduce the slurry concentration, and mix evenly to obtain mixture B4; S25. Add a second pH adjuster to mixture B4, and mix evenly to make the pH of the resulting mixture B5 10~11; S26. Add a second wetting agent to mixture B5, and mix evenly to obtain mixture B6; S27. Grind mixture B6, and grind it at least 6 times; S28. Add organic matter to the ground slurry, and mix evenly to obtain the second slurry.
[0042] Preferably, in S21, during the mixing process, the stirring rate is 500-600 rpm / min and the stirring time is 8-15 min.
[0043] Preferably, in step S22, during the mixing process, the stirring rate is 2000-2600 rpm / min, and the stirring time is 20-50 min.
[0044] Preferably, in step S23, during the mixing process, the stirring rate is 2000-2600 rpm / min, and the stirring time is 90-180 min.
[0045] Preferably, in step S24, during the mixing process, the stirring rate is 2000-2600 rpm / min, and the stirring time is 20-50 min.
[0046] Preferably, in S25, the amount of the second pH adjuster added is calculated to adjust the pH of the second slurry to 10-11.
[0047] Preferably, the second pH adjuster includes at least one of sodium hydroxide and sodium bicarbonate. Sodium hydroxide can be purchased from Sinopharm Group, model: AR (Shanghai Trial) (tablets), ≥96.0% 500g, Sinopharm code 10019718.
[0048] Preferably, in step S26, during the mixing process, the stirring rate is 10-15 rpm / min and the stirring time is 30-45 min.
[0049] Preferably, in S27, zirconium beads are used for grinding, and the size of the zirconium beads is 0.3~0.6mm.
[0050] Preferably, in step S28, during the mixing process, the stirring rate is 10~20 rpm / min and the stirring time is 20~45 min.
[0051] Preferably, the organic matter in the second slurry accounts for 0.5-3% of the total mass. Preferably, the organic matter in the second slurry accounts for 0.5-2% of the total mass. Preferably, the organic matter in the second slurry accounts for 1% of the total mass.
[0052] Preferably, in the second slurry, the mass ratio of the second binder, insulating material, second wetting agent, organic matter, and water is 5~15:15~25:0.2~0.8:0.5~3:100~200.
[0053] According to a third aspect of the present invention, an electrode is provided, comprising the above-described carbon-coated current collector or a carbon-coated current collector prepared by the above-described method for preparing the carbon-coated current collector.
[0054] According to a fourth aspect of the present invention, a battery is provided, comprising the above-described carbon-coated current collector, or comprising a carbon-coated current collector prepared by the above-described carbon-coated current collector preparation method, or comprising the above-described electrode sheet.
[0055] In summary, the present invention has the following advantages over the prior art: This invention introduces organic matter into the aqueous slurry used in the insulating areas on both sides of the carbon-coated current collector substrate. This organic matter can form a stable and continuous oily film on the surface of the aqueous slurry in the insulating area, thus effectively blocking the two types of aqueous slurry, namely the aqueous slurry in the carbon-coated area and the aqueous slurry in the insulating area. This effectively avoids the mutual solubility of the two types of aqueous slurry, thereby effectively ensuring the conductivity of the carbon-coated area and the insulation performance of the insulating areas (first insulating area and second insulating area), so that the battery prepared by the carbon-coated current collector has better electrochemical performance and insulation performance. Attached Figure Description
[0056] Figure 1 This is a schematic diagram of the sheet resistance of each region of the carbon-coated current collector after testing in this invention. Detailed Implementation
[0057] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0058] The material information used in the following examples and comparative examples is as follows: ① Aqueous acrylic acid (PAA, binder): available from Sinopharm Group, model: AR (Shanghai Test), ≥99.0% 500mL, Sinopharm code 80001418; ② Boehmite: available from Yishitong Technology, model: BG200; ③ Barium sulfate: available from Sinopharm Group, model: AR (Shanghai Test) 100g, Sinopharm code 10004416; ④ Dimethyl silicone oil: available from Sinopharm Group, model: H201-100 (Shanghai Test) 1kg, Sinopharm code 30235161.
[0059] Example 1 1. Preparation of the first slurry The first slurry of this embodiment was prepared according to the following steps: S11. Mix water with the first binder until homogeneous to obtain mixture A1; during the mixing process, the stirring rate is 500-600 rpm / min and the stirring time is 8-15 min; the first binder is PAA, which is added in the form of an emulsion, with a solid content of 15-30% and a viscosity of 800-3500 mPa.s; S12. Add the first part of the conductive agent to mixture A1, mix evenly to obtain mixture A2; during the mixing process, the stirring speed is 2000-2600 rpm / min, and the stirring time is 20-50 min; the first part of the conductive agent is 50% of the total mass of the conductive agent; the conductive agent is a composite conductive agent of carbon powder and graphite, and the mass ratio of carbon powder to graphite is 1:1; S13. Add the second part of the conductive agent to mixture A2, mix thoroughly to obtain mixture A3; during the mixing process, the stirring speed is 2000-2600 rpm / min, and the stirring time is 40-90 min; the second part of the conductive agent is 50% of the total mass of the conductive agent. S14. Add water to mixture A3 to reduce the slurry concentration. After mixing evenly, mixture A4 is obtained. During the mixing process, the stirring speed is 2000-2600 rpm / min and the stirring time is 20-50 min. S15. Add the first pH adjuster to mixture A4, mix thoroughly, and make the pH of the resulting mixture A5 5~7; the first pH adjuster is sulfuric acid; S16. Add the first wetting agent to mixture A5, mix evenly to obtain mixture A6; during the mixing process, the stirring speed is 10-15 rpm / min, and the stirring time is 30-45 min; the first wetting agent is modified polyether siloxane; S17. Homogenize mixture A6 twice, with the pressure of the homogenizing equipment being 300 bar during the homogenization process, to obtain the first slurry.
[0060] In the above steps, the stirring process can use a double-star stirred tank, but is not limited to this; the homogenization process can use a homogenizer, but is not limited to this.
[0061] Furthermore, in the above steps, the mass ratio of the first adhesive, conductive agent, first wetting agent, and water is 1~2:1~3:1~2:20~30. If the first adhesive is added as an emulsion, the above mass ratio is calculated based on the mass after removing the solvent.
[0062] 2. Preparation of the second slurry The second slurry of this embodiment is prepared according to the following steps: S21. Mix water and the second binder evenly to obtain mixture B1; during the mixing process, the stirring rate is 500-600 rpm / min and the stirring time is 8-15 min; the second binder is PAA, which is added in the form of an emulsion, and the solid content of the PAA emulsion is 15-30%, and the viscosity is 800-3500 mPa.s; S22. Add the first part of the insulating material to mixture B1, mix evenly to obtain mixture B2; during the mixing process, the stirring speed is 2000-2600 rpm / min, and the stirring time is 20-50 min; the first part of the insulating material is 50% of the total mass of the insulating material; the insulating material is a compound of boehmite and barium sulfate, and the mass ratio of boehmite to barium sulfate is 9:1; S23. Add the second part of the insulating material to mixture B2, mix thoroughly to obtain mixture B3; during the mixing process, the stirring speed is 2000-2600 rpm / min, and the stirring time is 90-180 min; the second part of the insulating material is 50% of the total mass of the insulating material. S24. Add water to mixture B3 to reduce the slurry concentration. After mixing evenly, mixture B4 is obtained. During the mixing process, the stirring speed is 2000-2600 rpm / min and the stirring time is 20-50 min. S25. Add a second pH adjuster to mixture B4, mix thoroughly, and make the pH of the resulting mixture B5 10-11; the second pH adjuster is sodium hydroxide; S26. Add the second wetting agent to mixture B5, mix thoroughly to obtain mixture B6; during the mixing process, the stirring speed is 10-15 rpm / min, and the stirring time is 30-45 min; the second wetting agent is modified polyether siloxane; S27. Grind the mixture B6 6 times using zirconium beads with a size of 0.3~0.6mm. S28. Add organic matter to the ground slurry, mix evenly to obtain a second slurry; during the mixing process, the stirring rate is 10-20 rpm / min, and the stirring time is 20-45 min; the organic matter is dimethyl silicone oil.
[0063] In the above steps, the stirring process can use a double-star mixing tank, but is not limited to this; the grinding process can use a sand mill, but is not limited to this.
[0064] Furthermore, in the above steps, the mass ratio of the second adhesive, insulating material, second wetting agent, organic matter, and water is 5~15:15~25:0.2~0.8:0.5~3:100~200. If the first adhesive is added as an emulsion, the above mass ratio is calculated based on the mass after removing the solvent. In this embodiment, the organic matter accounts for 1% of the mass of the second slurry.
[0065] 3. Preparation of carbon-coated current collectors The carbon-coated current collector of this embodiment was prepared according to the following procedure: Using aluminum foil as a substrate, the first slurry and the second slurry prepared above are simultaneously coated on both sides of the substrate to form a functional layer containing a first insulating region, a carbonized region, and a second insulating region arranged sequentially in the width direction of the substrate; wherein, the carbonized region is formed by using the first slurry, and the first insulating region and the second insulating region are formed by using the second slurry.
[0066] The coating thickness (on one side) of the first insulating area, the carbon coating area, and the second insulating area is 1 μm; the coating width of the first insulating area and the second insulating area is 5 mm; and the coating width of the carbon coating area is 200 mm.
[0067] Example 2 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0068] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the mass percentage of organic matter (i.e., dimethyl silicone oil) in the second slurry is adjusted to 0.5%, while the mass ratio of the second binder, insulating material, and second wetting agent remains unchanged. The rest is the same as in Example 1.
[0069] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0070] Example 3 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0071] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the mass percentage of organic matter (i.e., dimethyl silicone oil) in the second slurry is adjusted to 0.1%, while the mass ratio of the second binder, insulating material, and second wetting agent remains unchanged. The rest is the same as in Example 1.
[0072] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0073] Example 4 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0074] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the mass ratio of boehmite to barium sulfate in the insulating material is adjusted to 1:1. The rest is the same as in Example 1.
[0075] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0076] Example 5 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0077] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the mass ratio of boehmite to barium sulfate in the insulating material is adjusted to 6:4. The rest is the same as in Example 1.
[0078] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0079] Example 6 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0080] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that step S25 is omitted, i.e., pH adjustment is not performed during the preparation process. The rest is the same as in Example 1.
[0081] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0082] Example 7 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0083] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the organic dimethyl silicone oil is replaced with a perfluoropolyether oil. The rest is the same as in Example 1.
[0084] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0085] Example 8 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0086] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the organic compound dimethyl silicone oil is replaced with perfluorohexane. The rest is the same as in Example 1.
[0087] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0088] Example 9 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0089] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the organic dimethyl silicone oil is replaced with fluorinated silicone oil. The rest is the same as in Example 1.
[0090] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0091] Example 10 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0092] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the organic dimethyl silicone oil is replaced with a long-chain alkane (specifically, a polyα-olefin). The rest is the same as in Example 1.
[0093] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0094] Example 11 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0095] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the insulating material is changed to boehmite (i.e., the insulating material is only boehmite). The rest is the same as in Example 1.
[0096] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0097] Example 12 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0098] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the insulating material is changed to boehmite and zirconium oxide, and the mass ratio of boehmite to zirconium oxide is also 9:1. Everything else is the same as in Example 1.
[0099] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0100] Comparative Example 1 1. Preparation of the first slurry The preparation of the first slurry in this comparative example is the same as in Example 1.
[0101] 2. Preparation of the second slurry In this comparative example, the preparation of the second slurry differs from that in Example 1 in that no organic dimethyl silicone oil is added, i.e., step S28 is omitted. The rest is the same as in Example 1.
[0102] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this comparative example is the same as in Example 1.
[0103] Comparative Example 2 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0104] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the organic dimethyl silicone oil is replaced with polyvinyl chloride liquid plastic (polyvinyl chloride resin accounting for 15 wt%). The rest is the same as in Example 1.
[0105] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0106] Comparative Example 3 1. Preparation of the first slurry The preparation of the first slurry in this embodiment is the same as in Example 1.
[0107] 2. Preparation of the second slurry In this embodiment, the preparation of the second slurry differs from that in Example 1 in that the organic dimethyl silicone oil is replaced with polyethylene terephthalate liquid plastic (polyethylene terephthalate resin accounts for 15 wt%). The rest is the same as in Example 1.
[0108] 3. Preparation of carbon-coated current collectors The preparation of the carbon-coated current collector in this embodiment is the same as in Example 1.
[0109] Test case 1. Experimental Construction Method (1) The sheet resistance of the insulation region and the carbon-coated region of the carbon-coated current collectors prepared in all the above embodiments and comparative examples were tested, with reference to... Figure 1 , Figure 1 The carbon coating layer corresponds to the carbon coating area of the carbon-coated current collector in this invention, and the edge coating layer corresponds to the insulation area (first insulation area or second insulation area) of the carbon-coated current collector in this invention. Testing is mainly conducted in four areas: the middle carbon coating area, the carbon coating edge area, the edge coating edge area, and the middle edge coating area. (Refer to...) Figure 1 The red vertical box (test area) in the image shows the specific test steps as follows: a. Instrument calibration: After powering on and warming up, use a standard resistance element for calibration; b. Place the sample on an insulating platform (such as a glass or plastic plate) to ensure that there is no conductive contamination in the area in contact with the probe; c. The four probes are usually arranged in a straight line at equal intervals (common spacing is 1 mm) to ensure that the four probes simultaneously and perpendicularly contact the sample surface. d. Record the reading after stabilization. If the value fluctuates greatly, take multiple measurements and take the average value (e.g., 5 times).
[0110] (2) The surface tension, density and dielectric constant of the organic material used in the insulating region in all the above embodiments and comparative examples are described.
[0111] 2. Experimental Results The sheet resistance test results of each region of the carbon-coated current collector prepared in all the above embodiments and comparative examples, as well as the surface tension, density, and dielectric constant of the organic material used in the insulation region, are recorded in Table 1.
[0112] Table 1 shows the sheet resistance test results of each region of the carbon-coated current collectors prepared in the examples and comparative examples, as well as the surface tension, density, and dielectric constant of the organic materials used in the insulation region.
[0113] As shown in Table 1, the carbon-coated current collector provided by this invention has insulating regions on both sides of the substrate width direction. These insulating regions have low surface tension, less than 1.0 g / cm² at room temperature. 3 The organic matter, therefore, during the process of coating or applying the aqueous slurry for the carbonized area and the aqueous slurry for the insulating area to the middle and edges of the substrate respectively, forms an oil film. This oil film effectively blocks the two aqueous slurries, thus effectively preventing the mutual solubility of the two aqueous slurries, and thus effectively ensuring the conductivity of the carbonized area and the insulation performance of the insulating area. Referring specifically to the performance data of Examples 1-12, it can be found that the carbonized current collector provided by the present invention has a large sheet resistance in the edge area and a significantly small sheet resistance in the carbonized area. This ensures the conductivity of the carbonized area and the insulation performance of the insulating area required by the current collector, which is beneficial to ensuring the electrochemical performance and safety performance of the battery using the carbonized current collector.
[0114] In Comparative Example 1, no organic dimethyl silicone oil was added. In Comparative Examples 2 and 3, the surface tension of the organic material was too high, resulting in low sheet resistance in the middle and at the edges of the edge coating (insulation area) in Comparative Examples 1 to 3. As a result, the required insulation performance of the insulation area could not be effectively guaranteed, which would subsequently lead to a decrease in the safety performance and / or electrochemical performance of the battery using the carbon-coated current collector.
[0115] Further comparison of Examples 1 and Examples 2-3 shows that, compared to Example 1, the mass percentage of dimethyl silicone oil in Examples 2 and 3 is relatively small and relatively large, respectively, resulting in a decrease in the edge sheet resistance of the edge coating (insulation area). In particular, the decrease in the edge sheet resistance of the edge coating (insulation area) is significant in Example 3. This indicates that a mass percentage of 1% for dimethyl silicone oil is more conducive to improving the edge sheet resistance of the edge coating (insulation area) and obtaining an insulation area with good insulation performance.
[0116] Comparing Examples 1 and 4-5, and Examples 11-12, firstly, compared to Example 1, the insulating material in Example 11 was only boehmite, while the insulating material in Example 12 was a combination of boehmite and zirconium oxide. This resulted in a decrease in the edge sheet resistance of the edge coating (insulating area), which to some extent degraded the insulation performance of the current collector insulating area, thus negatively impacting the battery's safety or electrochemical performance. Secondly, compared to Example 1, the mass ratios of boehmite and barium sulfate in Examples 4 and 5 were 1:1 and 6:4, respectively. The performance results show that adjusting the ratio of boehmite to barium sulfate reduced the sheet resistance in the middle and at the edges of the edge coating (insulating area). This indicates that a mass ratio of boehmite to barium sulfate of 9:1 is more conducive to improving the resistance of the insulating area and optimizing its insulation performance.
[0117] Comparing Example 1 and Example 6, in Example 6, step S25 is not performed, that is, pH adjustment is not performed during the preparation process. This will also cause a decrease in the sheet resistance in the middle and at the edge of the edge coating (insulation area), and the insulation performance of the insulation area will be deteriorated.
[0118] Comparing Examples 1 and Examples 7-10, the types of organic materials in Examples 7-10 have changed, which has also led to a decrease in the sheet resistance in the middle and at the edges of the edge coating layer (insulation area), and an increase in the sheet resistance in the middle and at the edges of the carbon coating layer (carbon coating area). Therefore, it is not conducive to further optimization of the insulation performance of the insulation area and the conductivity performance of the carbon coating area.
[0119] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention, but such modifications or substitutions are all within the scope of protection of the present invention.
Claims
1. A carbon-coated current collector, characterized by: It includes a substrate and a functional layer disposed on at least one surface of the substrate; the functional layer includes a first insulating region, a carbon-coated region, and a second insulating region. In the width direction of the substrate, the first insulating area, the carbon coating area, and the second insulating area are arranged in sequence, and the first insulating area and the second insulating area are respectively located on the two sides of the width direction of the substrate; The first and second insulating regions contain an organic substance having a surface tension of 10 to 32 mN / m at normal temperature and a density of less than 1.0 g / cm 3 at normal temperature, the organic substance being dimethyl silicone oil. The preparation method of the carbon-coated current collector is as follows: On the surface of the substrate, a first aqueous slurry and a second aqueous slurry are simultaneously coated to form a functional layer containing a first insulating region, a carbonized region, and a second insulating region arranged sequentially in the width direction of the substrate. The carbon coating area is formed using the first aqueous slurry, and the first insulation area and the second insulation area are formed using the second aqueous slurry. The first aqueous slurry comprises a first binder, a conductive agent, a first wetting agent, and water; the mass ratio of the first binder, the conductive agent, and the first wetting agent is 1~2:1~3:1~2; The second aqueous slurry comprises a second binder, an insulating material, a second wetting agent, the organic matter, and water, wherein the mass ratio of the second binder, the insulating material, the second wetting agent, and the organic matter is 15~25:5~15:0.2~0.8:0.5~3.
2. The carbon coated current collector of claim 1, wherein: The dielectric constant of the organic compound is 1 to 5.
3. The carbon-coated current collector as described in claim 1, characterized in that: The dielectric constant of the organic compound is 2 to 3.
4. The carbon-coated current collector as described in claim 1, characterized in that: The first insulating region and the second insulating region also contain insulating material, wherein the mass ratio of the insulating material to the organic matter is 5~15:0.5~3.
5. The carbon-coated current collector as described in claim 1, characterized in that: The width of the first insulation area and the second insulation area is 1~5cm; the width of the carbon coating area is greater than or equal to 20cm.
6. The carbon-coated current collector as described in claim 4, characterized in that: The insulating material includes at least one of boehmite, barium sulfate, alumina, silicon carbide, silicon nitride, zirconium oxide, and boron oxide.
7. The carbon-coated current collector as described in claim 6, characterized in that: The insulating material includes boehmite and barium sulfate; and the mass ratio of boehmite to barium sulfate is 6~9:1~4.
8. The carbon-coated current collector as described in claim 7, characterized in that: The mass ratio of boehmite to barium sulfate is 9:
1.
9. The carbon-coated current collector as described in claim 1, characterized in that, Meet any of the following conditions: (1) The second aqueous slurry also includes a second solvent, wherein the surface tension difference between the second solvent and the organic matter is k, k = 30~60 mN / m; (2) The first aqueous slurry also includes a first solvent, wherein the surface tension difference between the first solvent and the organic matter is m, where m = 30~60 mN / m; (3) The second aqueous slurry further includes a second solvent, and the first aqueous slurry further includes a first solvent, with the surface tension difference between the second solvent and the first solvent being n, where n = 0~20 mN / m.
10. The carbon-coated current collector as described in claim 9, characterized in that, Meet any of the following conditions: (1) k = 50~60 mN / m; (2) m = 50~60 mN / m; (3) n = 0~5 mN / m.
11. A battery, characterized in that: Includes the carbon-coated current collector as described in any one of claims 1 to 10.
Citation Information
Patent Citations
Electrode sheet and method for manufacturing the same, secondary battery, battery module and battery pack
KR102735726B1
Electrode pole piece and preparation method therefor, secondary battery, battery module, and battery pack
WO2023130791A1